Dental care needs in the child population of a megapolis - S. B. Ulitovskiy; V. A. Grigoriev; E. V. Volokitina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
Based on the reports of examination preschool and school-aged children for the 2008-2014 year we can conclude that nowadays the issue of prevention of dental diseases among the inspected groups of children is actually